2015
DOI: 10.1016/j.bbamcr.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Cellular iron uptake, trafficking and metabolism: Key molecules and mechanisms and their roles in disease

Abstract: Iron is a crucial transition metal for virtually all life. Two major destinations of iron within mammalian cells are the cytosolic iron-storage protein, ferritin, and mitochondria. In mitochondria, iron is utilized in critical anabolic pathways, including: iron-storage in mitochondrial ferritin, heme synthesis, and iron-sulfur cluster (ISC) biogenesis. Although the pathways involved in ISC synthesis in the mitochondria and cytosol have begun to be characterized, many crucial details remain unknown. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
270
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(280 citation statements)
references
References 147 publications
(326 reference statements)
7
270
1
2
Order By: Relevance
“…In contrast, patients with underlying autoimmune disorders and/or hematologic malignancies demonstrate a loss of central tolerance and differentiation blocks 6 ; these patients have poor and short-lived responses to immune-directed therapy because additional cell types are involved in disease pathogenesis and the implicated lymphocyte repertoire is largely autoreactive and able to reconstitute rapidly after therapy (see figure). As demonstrated by this and other reports, 7,8 combination therapy directed at multiple arms of the immune response, along with TRAs, improves response rates. This is an important observation, though treatment of refractory ITP nevertheless remains reminiscent of the story of the "blind men and the elephant," in which a group of blind men touch different parts of an elephant, and when they compare notes find they are in complete disagreement.…”
mentioning
confidence: 78%
“…In contrast, patients with underlying autoimmune disorders and/or hematologic malignancies demonstrate a loss of central tolerance and differentiation blocks 6 ; these patients have poor and short-lived responses to immune-directed therapy because additional cell types are involved in disease pathogenesis and the implicated lymphocyte repertoire is largely autoreactive and able to reconstitute rapidly after therapy (see figure). As demonstrated by this and other reports, 7,8 combination therapy directed at multiple arms of the immune response, along with TRAs, improves response rates. This is an important observation, though treatment of refractory ITP nevertheless remains reminiscent of the story of the "blind men and the elephant," in which a group of blind men touch different parts of an elephant, and when they compare notes find they are in complete disagreement.…”
mentioning
confidence: 78%
“…Apo-Isu1 does not appear to bind iron at the active site with significant affinity (58), suggesting that iron may be actively delivered to the ISC complex. Yfh1 and its human homologue frataxin can bind ferrous iron via acidic residues on the N-terminal ␣-helix, but concrete in vivo evidence of Yfh1 supplying iron is still lacking (15,59). Interestingly, frataxin-independent cluster synthesis using an Isu1 mutant protein may rule against a specific iron delivery function of frataxin (60).…”
Section: De Novo Synthesis Of a [2fe-2s] Cluster On The Mitochondrialmentioning
confidence: 99%
“…Cells typically maintain a strict balance of iron and sulfide ion concentrations due to their damaging redox reactions when present in excess (14,15). The cell also uses a complex biosynthetic system to ensure that the sometimes redox-sensitive and labile Fe/S clusters are assembled correctly, trafficked to specific target apoproteins, and remain protected during these processes.…”
Section: Ubiquitous Iron-sulfur Clusters and Their Synthesis: An Overmentioning
confidence: 99%
“…2 These concepts proved prescient as they have been supported by a number of recent findings which have shown that the macrophage-erythroblast interactions mediated by a large number of adhesion molecules are essential for the highly regulated process of erythroblast proliferation and survival which is necessary for the production of two million reticulocytes per second. [3][4][5][6] In this context the recent findings that in vivo depletion of erythroblastic island macrophages blocks erythroblast proliferation and maturation fully validates the central role of macrophages in regulating erythropoiesis. 7 Apart from playing an important role in the genesis of red blood cells within the bone marrow, macrophages of the reticulocyte endothelial system in general and spleen in particular play a critical role in quality control by removing senescent and damaged red cells from the circulation.…”
mentioning
confidence: 99%
“…The exact route of uptake of NTBI remains unclear, but it is well established that NTBI is responsible for parenchymal cell iron overload. 1,5 β-thalassemia is a congenital anemia characterized by ineffective erythropoiesis, increased Tf saturation and tissue iron overload. 6 It represents a paradigmatic disorder of erythropoiesis characterized by anemia and dysfunction of iron homeostasis.…”
mentioning
confidence: 99%